Patient predictors of health-seeking behaviour for persons coughing for more than two weeks in high-burden tuberculosis communities: the case of the Western Cape, South Africa - Carmen Christian; Cobus Burger; Mareli Claassens; Virginia Bond; Ronelle Burger (BMC, 2019)
Abstract Background This study aimed to analyse the patient predictors of health-seeking behaviour for persons coughing for more than 2 weeks to better understand this vulnerable and important population. Methods The study analysed data from a cohort study (SOCS - Secondary Outcome Cohort Study) embedded in a community randomised trial ZAMSTAR (Zambia and South Africa TB and AIDS Reduction Study) in eight high-burden TB communities in the Western Cape, South Africa. These datasets are unique as they contain TB-related data as well as data on health, health-seeking behaviour, lifestyle choices, employment, socio-economic status, education and stigma. We use uni- and multivariate logistic regressions to estimate the odds ratios of consulting for a cough (of more than 2 weeks duration) for a range of relevant patient predictors. Results Three hundred and forty persons consulted someone about their cough and this represents 37% of the 922 participants who reported coughing for more than 2 weeks. In the multivariate analysis, respondents of black ethnic origin (OR 1.99, 95% CI 1.28-3.12, P < 0.01), those with higher levels of education (OR 1.05 per year of education, 95% CI 1.00-1.10, P = 0.05), and older respondents (OR 1.02 per year, 95% CI 1.01-1.04, P < 0.01) had a higher likelihood of consulting for their chronic cough. Individuals who smoked (OR 0.63, 95% CI 0.45-0.88, P < 0.01) and those with higher levels of socio-economic status (OR 0.81, 95% CI 0.71-0.92, P < 0.01) were less likely to consult. We find no evidence of stigma playing a role in health-seeking decisions, but caution that this may be due to the difficulty of accurately and reliably capturing stigma due to, amongst other factors, social desirability bias. Conclusions The low levels of consultation for a cough of more than 2 weeks suggest that there are opportunities to improve case-finding. These findings on health-seeking behaviour can assist policymakers in designing TB screening and active case-finding interventions that are targeted to the characteristics of those with a chronic cough who do not seek care.